Non-Conviction-Based Asset Forfeiture: Presumption of Innocence and Principle of Legality Perspective - Muhammad Nurul Huda; Safira Ila Mardhatillah; Qurota Ayunisa; Amrina Munjiyah; Afrizal Eko Nugroho (Walisongo Law Review (Walrev), 2025)
This research aims to examine the legality of the Non-Conviction-Based Asset Forfeiture (NCBAF) provisions in the Draft Law on Asset Forfeiture. The research is motivated by the limitations of conviction-based forfeiture in cases where offenders have died, fled, or cannot be prosecuted, resulting in unrecovered state losses. NCBAF provides an alternative through an in-rem mechanism, allowing the state to pursue assets suspected of being the proceeds of crime without first waiting for a criminal conviction. Terminologically, in rem proceedings are directed at the property itself, while in personam proceedings are directed at an individual to establish guilt and impose punishment. This distinction is essential, as NCBAF focuses on the asset as the object of dispute rather than the criminal liability of the owner, thereby requiring careful adaptation within Indonesia’s civil law framework to remain consistent with the principles of legality and presumption of innocence. This research employs a normative juridical method, incorporating both statutory and conceptual approaches. The findings indicate that NCBAF can be constitutionally justified if explicitly regulated by law, placed under judicial oversight, and accompanied by legal protection for bona fide third parties. Therefore, the Asset Forfeiture Bill is a strategic legal instrument to strengthen asset recovery in Indonesia in a manner that is effective, fair, and consistent with fundamental principles of national criminal law. Penelitian ini bertujuan untuk mengkaji legalitas ketentuan Perampasan Aset Berbasis Non-Conviction (NCBAF) dalam Rancangan Undang-Undang Perampasan Aset. Penelitian ini dilatarbelakangi oleh keterbatasan perampasan berbasis putusan dalam kasus-kasus di mana pelaku telah meninggal dunia, melarikan diri, atau tidak dapat dituntut, sehingga mengakibatkan kerugian negara yang belum terpulihkan. NCBAF memberikan alternatif melalui mekanisme in rem, yang memungkinkan negara untuk mengejar aset yang diduga merupakan hasil kejahatan tanpa terlebih dahulu menunggu putusan pidana. Secara terminologis, proses in rem ditujukan pada properti itu sendiri, sementara proses in personam ditujukan pada individu untuk menetapkan kesalahan dan menjatuhkan hukuman. Perbedaan ini penting, karena NCBAF berfokus pada aset sebagai objek sengketa, alih-alih pertanggungjawaban pidana pemiliknya, sehingga memerlukan adaptasi yang cermat dalam kerangka hukum perdata Indonesia agar tetap konsisten dengan asas legalitas dan praduga tak bersalah. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan perundang-undangan dan konseptual. Temuan penelitian menunjukkan bahwa NCBAF dapat dibenarkan secara konstitusional jika diatur secara tegas dalam undang-undang, berada di bawah pengawasan peradilan, dan disertai dengan perlindungan hukum bagi pihak ketiga yang bonafide. Oleh karena itu, RUU Perampasan Aset merupakan instrumen hukum yang strategis untuk memperkuat pemulihan aset di Indonesia secara efektif, adil, dan konsisten dengan prinsip-prinsip dasar hukum pidana nasional. Keywords: Non-Conviction Based Asset Forfeiture; Presumption of Innocence; Legality.